Athletes' Perception of Leadership According to Their Perceptions of Goal Achievement and Sport Results. Issue 2 (April 2020) - Gomes, A. Rui; Almeida, Albino; Resende, Rui
In this study, we investigated whether athletes' perceptions of coaches' leadership differ according to their perceptions of individual and team goal achievement and their sport performance. We collected data at the beginning and end of the sport season from 180 soccer players (aged 16–18 years). We evaluated three leadership areas (transformational, transactional, and decision-making) and the participants' perceptions of individual and team performance during the sport season. Our results showed that (a) athletes with perceptions of higher individual goal achievement evaluated their coaches more positively, (b) athletes with perceptions of higher team goal achievement started the sport season with a less positive evaluation of their coaches but ended the season with a more positive coach evaluation, and (c) athletes with higher sport performance evaluated their coaches less positively in two domains of transformational leadership but ended the season by attributing less negative feedback and passive management to their coaches. In conclusion, these athletes' evaluations of coaches' leadership behaviors differed according to their perceptions of goal achievement and their own sport performance.